PENGGUNAAN MEDIA ULAR TANGGA DAN KARTU TANTANGAN BERBASIS AUGMENTED REALITY (AR) PADA PEMBELAJARAN IPAS - Yolanda Ismail; Razak H. Umar; Aljunaid Bakari (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to improve the critical thinking skills of fourth grade students of MIS Muhammadiyah Pone in the science learning of My Role in the School and Community Environment through the use of snakes and ladders media and challenge cards based on Augmented Reality (AR). This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model consisting of planning, action implementation, observation, and reflection stages carried out in two cycles. The results of the study showed an increase in students' critical thinking skills in each cycle. In the pre-cycle stage, 4 students or 33.33% achieved learning mastery with an average class score of 66.25. In cycle I, the number of students who completed increased to 8 students or 66.67% with an average class score of 77.08. Furthermore, in cycle II the number of students who completed increased to 11 students or 91.67% with an average class score of 87.08. The results of observations of teacher and student activities also showed an increase in each meeting. The improvement shows that the use of snakes and ladders media and Augmented Reality (AR) based challenge cards is able to create a more active, interesting learning atmosphere, and encourage students to think critically in solving problems related to the learning material.